2021
DOI: 10.1186/s12889-021-10622-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional trend analysis of the NCHA II survey data on Canadian post-secondary student mental health and wellbeing from 2013 to 2019

Abstract: Background Canadian post-secondary students are considered to be at risk for chronic stress and languishing mental health, but there has been no longitudinal analysis of the available population-level data. The purpose of this study was to examine trends in the overall and sex-specific prevalence of self-reported stress, distress, mental illness, and help seeking behaviours among Canadian post-secondary students over the past several years. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Table 6 summarizes participants comprehension-related feedback for each tool section, followed by the study teams agreed upon modifications. Overall, we found students in later sessions (5)(6) affirmed and supported content modifications made in response to concerns raised in earlier sessions (1)(2)(3)(4).…”
Section: Understandability-relatedsupporting
confidence: 66%
See 1 more Smart Citation
“…Table 6 summarizes participants comprehension-related feedback for each tool section, followed by the study teams agreed upon modifications. Overall, we found students in later sessions (5)(6) affirmed and supported content modifications made in response to concerns raised in earlier sessions (1)(2)(3)(4).…”
Section: Understandability-relatedsupporting
confidence: 66%
“…In recent years, post-secondary students have reported increasing levels of mental health challenges including psychological distress and diagnosed conditions (e.g., anxiety, depression) ( 1 ). While the post-secondary years are often a period of self-exploration and interpersonal growth ( 2 ), they have also been associated with high stress, peer pressure, and greater responsibilities with reduced social supports ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has raised global concerns around the potential of a rising mental health pandemic and has brought increased awareness to the need for mental health support [2]. Yet, cross-sectional analysis of survey data on Canadian post-secondary student mental health and well-being showed that the proportion of students self-reporting mental health related challenges, including stress, psychological distress, and diagnosed mental illnesses were already on the rise from 2013 to 2019, prior to the pandemic [14]. Another pre-pandemic study by Fischman and Gardner interviewed 2,000 stakeholders from 10 educational institutions across the United States starting in 2012 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of mental illnesses among post-secondary students are not significantly different from those observed among the general Canadian population [ 1 ], the demand for mental health services on post-secondary campuses continues to grow as does the complexity of presenting issues [ 2 ]. National cross-sectional data suggests that the prevalence of students reporting above average to extreme levels of stress is increasing, along with self-reported symptoms of common mental illnesses such as anxiety and depression [ 3 ]. Chronic stress has been linked to poor academic performance and negative mental health outcomes [ 4 ], necessitating the bolstering of upstream campus services that provide students with the tools needed to recognize and respond to changes in their mental health in the face of day-to-day stressors.…”
Section: Introductionmentioning
confidence: 99%